Hubungan Tingkat Pengetahuan dengan Motivasi Orang Tua dalam Melaksanakan Oral Hygiene pada Anak Usia 7-12 Tahun di Ruang Flamboyant RSUD Dr. Doris Sylvanus Palangka Raya: The Relationship Between the Level of Knowledge and Motivation of Parents in Carrying Out Oral Hygiene in Children Aged 7-12 Years in Flamboyant Room RSUD Dr. Doris Sylvanus Palangka Raya - Dessy Hertati; Vita Natalia; Ayu Nancyana; Vina Agustina; Siti Santy Sianipar (Jurnal Surya Medika (JSM), 2022)
Oral hygiene is an act of care needed to keep the mouth in good condition. Children aged 7-12 years do not have good self-maintenance behavior, so they need parental supervision, including oral hygiene maintenance. Parental knowledge is very important in supporting oral hygiene in children. This knowledge can be obtained naturally or planned through the educational process. The high knowledge of parents about oral hygiene has a major impact on the health of the oral cavity in children. The purpose of the study was to determine the relationship between the level of knowledge and parents' motivation in carrying out oral hygiene in children aged 7-12 years in the Flamboyant room of RSUD dr. Doris Sylvanus Palangka Raya 2019. This research method is correlated with the sampling method, namely purposive sampling. Respondents took as many as 30 mothers with children aged 7-12 years. Data analysis used the chi-square test, which showed a significant relationship between knowledge and parental motivation in carrying out oral hygiene in children aged 7-12 years, with the study's results showing sufficient knowledge of 80% and motivation of 77%. The analysis results with the chi-square test obtained 0.001, which is sig. (2-tailed) < 0.05. The results of this study are that there is a relationship between the level of knowledge and parents' motivation in carrying out oral hygiene in children aged 7-12. The conclusion is that motivation from the family is needed, especially parents, to always emphasize to children that oral hygiene is important to do every day to avoid the accumulation of food debris so that oral hygiene is maintained.